Understanding the Impact of Paediatric Asthma on Families: Development of a Theoretical Model. Issue 4 (19th February 2018) - Dudeney, Joanne; Sharpe, Louise; Hunt, Caroline
Abstract : The experience of paediatric asthma is associated with increased stress and emotional difficulties for both the child and family. The current study aimed to qualitatively explore parents' views of their child's asthma experience, from initial diagnosis onwards, to enhance our understanding of how families emotionally adjust and adapt to the diagnosis and management of asthma. Semi-structured interviews were conducted with 17 parents of children (<18 years) with physician-diagnosed asthma. Questionnaires were used to capture demographic information and anxiety symptom status of parents (State Trait Anxiety Inventory — Form Y [STAI-Y1/Y2]) and children (Spence Children's Anxiety Scale — Parent reported [SCAS-P]). Grounded theory was used to analyse the results. Analysis saw three themes emerge as important in understanding the impact of asthma on the family: (1) the experience of obtaining an asthma diagnosis, (2) parents' belief in their competence to manage asthma, and (3) parents' behaviour in response to the asthma. A model was developed that posits adaptive parental adjustment to asthma is determined in part by the circumstances around the time of diagnosis, the level of knowledge and skills, and the controllability of the asthma. This model can guide medical and allied health professionals to specific areas where intervention may reduce stress and emotional difficulties associated with asthma and its management for affected families.